HISTORY OF ART AND ITS TYPES - Viloyat Rajabovna Tuxsanova (Scholar Express Journal, 2021)
This article focuses on the history of applied art and its types. Based on the results of his many years of research, the author gives specific recommendations and ways to ensure the further development of folk arts and crafts.
Keywords: Folk Arts; Types Of Art; Cultural Heritage; Artistic And Creative Activity